2022
DOI: 10.1085/jgp.202213131
|View full text |Cite
|
Sign up to set email alerts
|

The archaeal glutamate transporter homologue GltPh shows heterogeneous substrate binding

Abstract: Integral membrane glutamate transporters couple the concentrative substrate transport to ion gradients. There is a wealth of structural and mechanistic information about this protein family. Recent studies of an archaeal homologue, GltPh, revealed transport rate heterogeneity, which is inconsistent with simple kinetic models; however, its structural and mechanistic determinants remain undefined. Here, we demonstrate that in a mutant GltPh, which exclusively populates the outward-facing state, at least two subs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 83 publications
(133 reference statements)
2
12
1
Order By: Relevance
“…The deviation from the 1:1 model indicates a complex binding behavior, which is maybe not surprising considering that at least two separate binding interfaces (stator/N-lobe and elevator/C-lobe) are involved, combined with the conformational flexibility of the participating molecules. Similar observations of complex binding events in transport mechanisms have been made with the BtuCD-BtuF ABC transporter 65 or the GltPh elevator-type transporter 66 . Clearly, more detailed experiments are needed to fully understand the binding kinetics of the tripartite complex.…”
Section: Resultssupporting
confidence: 73%
“…The deviation from the 1:1 model indicates a complex binding behavior, which is maybe not surprising considering that at least two separate binding interfaces (stator/N-lobe and elevator/C-lobe) are involved, combined with the conformational flexibility of the participating molecules. Similar observations of complex binding events in transport mechanisms have been made with the BtuCD-BtuF ABC transporter 65 or the GltPh elevator-type transporter 66 . Clearly, more detailed experiments are needed to fully understand the binding kinetics of the tripartite complex.…”
Section: Resultssupporting
confidence: 73%
“…To understand the structural origin of this state, we imaged TBOA-bound RSMR by cryo-EM. Following particle alignment with imposed C3 symmetry, we performed symmetry expansion and three-dimensional (3D) classification to sort multiple conformations of the transporter protomers. , We observed 91% protomers in the IFS with a wide-open substrate-binding site occupied by TBOA (Figures b and S6, and Table S1; see the Materials and Methods Section for data processing details). The remaining protomers were in the OFS, similar to the TBOA-bound WT (RMSD of 0.646 Å).…”
Section: Resultsmentioning
confidence: 99%
“…Introducing these and similar mutations in GltPh can reduce Na + binding and diminish coupling in some cases (10,(36)(37)(38). Though the proton carrier residues of GT-H are unknown, we previously suggested that a glutamate residue at the GltPh S279 position at the tip of HP1, conserved in GT-H, is a candidate (36). These sequence changes do not explain how a high-affinity substrate-binding site forms in a Na + -independent manner in GT-H and whether substrate binding to GT-H is H + -dependent or H + -coupling occurs through a different mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, coupled binding and transport occur because the high-affinity substrate binding state is a high-energy state only accessible when Na + binds. Accordingly, mutations in all three Na + -binding sites diminish coupled substrate binding and transport (3,6,(33)(34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%